Evaluation the Effectiveness of the Kampus Mengajar Program in Enhancing Student Motivation - Simangunsong, Herlina; Ginting, Bena br; Tarigan, Hermelina Eka Sari br; Sembiring, Dinaria br; Kaban, Debi Yolanda; Siregar, Christyani (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
This study aims to evaluate the effectiveness of the Kampus Mengajar Program in enhancing elementary school students' learning motivation in rural areas, with a case study at SD 040443 Kabanjahe. The program is part of the Merdeka Belajar–Kampus Merdeka (MBKM) policy, which involves university students as assistant teachers in schools facing limited educational resources. The study employed a quantitative approach with a quasi-experimental design (one-group pretest-posttest design), involving 94 students as respondents. The analysis results showed a significant increase in students' learning motivation scores from a pretest average of 64.37 to a posttest average of 81.35, with a p-value < 0.05 in the Wilcoxon Signed-Rank test and an effect size of 0.88, indicating a large effect. Additionally, observations and interviews revealed increased student participation, interest, and confidence in learning. These findings suggest that the Kampus Mengajar Program is effective in creating a learning environment that supports students’ intrinsic motivation and is relevant as a community-based educational intervention model that can be applied in various global contexts facing similar educational challenges.